Eucommia ulmoides Polysaccharides Attenuate Rabbit Osteoarthritis by Regulating the Function of Macrophages - Sun, Yaqiong; Huang, Kui; Mo, Linhai; Ahmad, Akhlaq; Wang, Dejia; Rong, Zijie; Peng, Honghui; Cai, Honghua; Liu, Guihua (Frontiers in Pharmacology, 2021)
Background and purpose: Eucommia ulmoides polysaccharides (EUP) can regulate the immunity of macrophages, but the functional status of macrophages is related to osteoarthritis and synovial inflammation. The purpose of this study is to explore whether EUP has the effect of inhibiting osteoarthritis and its possible mechanism. Methods: MTT test was used to evaluate the appropriate concentration of EUP and real-time quantitative polymerase chain reaction (RT-qPCR) was conducted to detect the effect of EUP on gene expression in RAW 264.7 cells. The osteoarthritis model was constructed by the anterior cruciate ligament transection (ACLT) in the rabbits. These rabbits were divided into 3 groups, sham operation group, OA group, and EUP group. The changes in articular cartilage were detected by gross observation and histological staining, and Micro-CT tested subchondral bone. Finally, the changes of macrophages in synovial tissue were studied by immunohistochemistry. Results: The results showed that EUP at the concentration of 50ug/mL and 100ug/mL were beneficial to the proliferation of macrophages. The qPCR results indicated that EUP inhibited the expression of inflammation-related genes IL-6, IL-18 and IL-1β, and promoted the expression of osteogenic and cartilage-related genes BMP-6, Arg-1 and transforming growth factor beta (TGF-β). The results of in vivo experiments suggested that the degree of destruction of articular cartilage in the EUP group was significantly reduced, and the Osteoarthritis Research Society International (OARSI) score was significantly reduced. Compared with the OA group, the subchondral cancellous bone density of the EUP group increased, the number and thickness of trabecular bone increased, and the separation of trabecular bone decreased. Synovial macrophage immunohistochemistry results manifested that EUP, on the one hand, reduced M1 polarized macrophages, on the other hand, accumulated M2 polarized macrophages. Conclusion: EUP can promote articular cartilage repair and subchondral bone reconstruction. The regulation of the polarization state of macrophages may be one of its mechanisms to delay the progression of osteoarthritis.